Ethnomycological study of edible and medicinal mushrooms in Menge District, Asossa Zone, Benshangul Gumuz Region, Ethiopia - Rediet Sitotaw; Ermias Lulekal; Dawit Abate (BMC, 2020)
Abstract Background Menge District has long been inhabited by people who have a long tradition of using wild mushrooms mainly as food, source of income, and medicine. Extensive utilization of wild edible mushrooms (WEM) coupled with an ever-increasing population growth, deforestation, and agricultural land expansion threatens fungal diversity and WEM in the area. Hence, this study is aimed at documenting and analyzing the ethnomycological knowledge of the people in order to preserve the dwindling WEM wealth and associated indigenous knowledge. Methods Ethnomycological data were collected using semi-structured interviews, focus group discussions, participant observations, and walk-in-the-woods methods. Statistical tests were used to compare the indigenous knowledge and practice of wild mushroom among different informant categories using One-way ANOVA and t tests. Results A total of 20 ethnomycologically important wild mushroom species belonging to ten genera and six families were identified, of which 15 were reported to be edible in the District. The family Lyophyllaceae was represented by the highest number of species (nine species, 45%) followed by Agaricaceae (seven species, 35%) and each of the remaining four families had single species representation. Significant difference (P < 0.05) was observed on the mean number of WEM reported among different group of respondents. Wild edible mushroom collection habit and practice was significantly (P < 0.05) influenced by gender, age, and literacy level. The output of preference ranking exercise indicated Termitomyces schimperi was ranked first followed by Termitomyces letestui, Termitomyces microcarpus, and Termitomyces eurhizusas as the most preferred edible mushrooms respectively. Conclusion The present study shows that Menge District is rich in wild mushroom diversity and associated indigenous knowledge. However, anthropogenic factors together with loss of indigenous knowledge and very poor conservation efforts threaten the survival of economically and ecologically important mushrooms in the area. Thus, complementary in situ and ex situ mushroom conservation strategy is highly recommended.